2017
DOI: 10.5455/aim.2017.25.232-235
|View full text |Cite
|
Sign up to set email alerts
|

The Most Common Smartphone Applications Used By Medical Students and Barriers of Using Them

Abstract: Introduction:Medical knowledge is rapidly expanding and updating. It is very important that students can timely access to information and the latest scientific evidence without any time and place limitation. The smartphone is one of ICT tools that adopted greatly by healthcare professionals. Today, the most medical sciences universities have provided smartphone as an educational aid tool and acquisition licenses for medical apps resources in training of their students.Aim:This research was conducted to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
(32 reference statements)
2
25
1
Order By: Relevance
“…The results of this study indicate that most of the primary health care professionals surveyed were using apps to access SNSs in a professional context and that WhatsApp, Twitter, and Facebook, in this order, were the most used, in both personal and professional contexts [20,29]. In terms of its benefits, WhatsApp was generally perceived as more useful for improving professional knowledge and clinical problem solving [13].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that most of the primary health care professionals surveyed were using apps to access SNSs in a professional context and that WhatsApp, Twitter, and Facebook, in this order, were the most used, in both personal and professional contexts [20,29]. In terms of its benefits, WhatsApp was generally perceived as more useful for improving professional knowledge and clinical problem solving [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are many challenges that students face with regard to health education, especially medical sciences students with complex health care services process. 1,2 It is very important that students can have quick and timely access to information such as clinical guidelines, drug resources, clinical calculations, and latest scientific evidence without any time and place limitations, [3][4][5] and also, the potential of mobile technologies to be used in accessing learning resources in the health care setting for the continuous acquisition of new knowledge, skills, and attitudes to enable competent practice (including podcasting, video casting, and library resources). 6 Thus, to meet these needs, using information and communication technology (ICT) seems to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies have reported on the utility of online educational resources, instructional videos services, teaching platforms, and smart phone / tablet applications that supplement medical training curricula. [6][7][8] With the advent of social media and growing online presence of physicians, educators, and trainees, medical students may remain connected to clinical learning albeit through a computer or smartphone screen.…”
Section: Résumémentioning
confidence: 99%